1961
DOI: 10.1111/j.1476-5381.1961.tb01119.x
|View full text |Cite
|
Sign up to set email alerts
|

Anthelmintic Activity of Methyridine Against Experimental Nematode Infections in Mice

Abstract: Critical studies using mice infected experimentally with nematodes (Nematospiroides dubius, Nippostrongylus muris and Heterakis spumosa) have shown methyridine to be an extremely effective anthelmintic when administered orally or subcutaneously. Comparisons of the two treatment regimes show subcutaneous administration to be the more efficient in terms of absolute dose, but neither treatment has a significant advantage in therapeutic safety margin. Methyridine has a more uniform anthelmintic action than either … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1961
1961
2003
2003

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Methyridine was also observed to have a rapid paralyzing effect on intact nematode parasites in vitro , demonstrating that methyridine passes through the cuticle to get to the neuromuscular system. The effect of methyridine (10 μ g ml −1 =73 μ M ) on A. suum segments (Broome, 1961) was complete paralysis within 2 min. Interestingly, the effects were observed rapidly after applying methyridine to the preparation, and not reversed by the addition of acetylcholine and decamethonium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Methyridine was also observed to have a rapid paralyzing effect on intact nematode parasites in vitro , demonstrating that methyridine passes through the cuticle to get to the neuromuscular system. The effect of methyridine (10 μ g ml −1 =73 μ M ) on A. suum segments (Broome, 1961) was complete paralysis within 2 min. Interestingly, the effects were observed rapidly after applying methyridine to the preparation, and not reversed by the addition of acetylcholine and decamethonium.…”
Section: Discussionmentioning
confidence: 99%
“…Although a number of studies have characterized the range of parasites that methyridine is effective against, information concerning the mode of action of this compound is incomplete and based on three studies. Broome (1961) first suggested that the mode of action of methyridine was as a neuromuscular blocking agent; and then Eyre (1970), using rat isolated phrenic nerve diaphragm and chick isolated biventer cervicis muscle preparations, observed that methyridine behaved like the depolarizing muscle relaxant, succinylcholine. However, in the most recent study ( Raymond et al , 2000 ), methyridine in concentrations up to 1 m M was reported to have no effect on two AChR subtypes (chicken α ‐7 and C. elegans ACR‐16) expressed in Xenopus oocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Anthelmintic studies in laboratory animals (Broome & Greenhalgh,. 1961b) have shown that the drug is a more efficient anthelmintic when administered subcutaneously than when given orally.…”
Section: Discussionmentioning
confidence: 99%
“…Blood and gut concentrations of methyridine in mice. Groups of 20 mice were dosed with the optimum therapeutic dose of methyridine 400 mg/kg orally and subcutaneously (Broome & Greenhalgh, 1961b). After the appropriate time interval all animals were sacrificed and their blood was collected together with material from various regions of the alimentary canal.…”
mentioning
confidence: 99%
See 1 more Smart Citation